Unveiling The Dynamics Of Firm Value In The Consumer Non-Cyclicals Sector: The Role Of Firm Size, Accounting Conservatism, And Tax Avoidance - Darmawana, Akbar Fajar Muhammad; Sukarnob, Edy; Akbar, Taufiq (West Science Accounting and Finance, 2025)
This study examines the impact of tax avoidance, accounting conservatism, and business size affect firm value in Indonesia Stock Exchange-listed consumer non-cyclicals manufacturing from 2019 to 2023. Despite the sector's theoretical defensiveness, macroeconomic pressures and market sentiment volatility drove stock indices down, emphasizing the necessity to study corporate valuation issues. The study employs panel data regression analysis on a purposive sample of 36 companies to assess accounting conservatism through accrual-based metrics, tax avoidance via effective tax rates, and firm size using the natural logarithm of total assets, with firm value represented by price-to-book value (PBV). The findings demonstrate that accounting conservatism and tax avoidance do not significantly influence firm value, indicating that investors choose genuine profitability and growth over conservative reporting or tax techniques in this sector. Conversely, firm size positively influences firm value, likely due to larger firms’ greater operational efficiency, resource accessibility, and market reputation, despite the potential challenges of agency costs and management complexity. These findings provide valuable insights for investors and managers in consumer non-cyclicals manufacturing, emphasizing the importance of scale over accounting policies and tax avoidance in shaping market valuation under uncertain economic conditions.